2017
DOI: 10.1161/circulationaha.116.026858
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged, Uninterrupted Sedentary Behavior and Glycemic Biomarkers Among US Hispanic/Latino Adults

Abstract: Background Excessive sedentary time is ubiquitous in developed nations and is associated with deleterious health outcomes. Few studies have examined whether the manner in which sedentary time is accrued (in short or long bouts) carries any clinical relevance. The purpose of this study was to examine the association of prolonged-uninterrupted sedentary behavior with glycemic biomarkers in a cohort of U.S. Hispanic/Latino adults. Methods We studied 12,083 participants from the Hispanic Community Health Study/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 34 publications
3
55
1
1
Order By: Relevance
“…In fact, participants in the present research accumulated~27% of total ST in bouts ≥ 30 min. Other previous study in adults confirmed that approximately 40% of total ST was accrued in bouts > 30 min, with 70% of participants accruing at least 1 sedentary bout per day > 60 [3]. In the current study, 94% of participants accumulated at least one sedentary bout per day ≥ 30, whereas only 22% accumulated at least one sedentary bout per day ≥ 60.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In fact, participants in the present research accumulated~27% of total ST in bouts ≥ 30 min. Other previous study in adults confirmed that approximately 40% of total ST was accrued in bouts > 30 min, with 70% of participants accruing at least 1 sedentary bout per day > 60 [3]. In the current study, 94% of participants accumulated at least one sedentary bout per day ≥ 30, whereas only 22% accumulated at least one sedentary bout per day ≥ 60.…”
Section: Discussionsupporting
confidence: 78%
“…Evidence suggests that frequently interrupting prolonged bouts of ST is a way to improve cardio-metabolic outcomes [44,45], obesity [46] or glucose levels [3] in diverse populations. In older adults, uninterrupted ST lasting ≥ 30 min was associated with increased frailty independent of total ST and bouted MVPA [47].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations